BUDGETARY SLACK ATAS INTERAKSI TEKANAN KETAATAN, REINFORCEMENT CONTINGENCY DAN MORAL EQUITY SUBORDINATE - Fara Fitriyani (Tirtayasa Ekonomika, 2018)
This study aims to determine the effect of obedience pressureon budgetary slack and the interaction between obedience pressure, moral equity,and reinforcement contingency on budgetary slack.The population of this study is subordinate in universities in Banten Province. The sampling method using purposive sampling with the number of samples that meet the criteria of 91 respondents. The questionnaire was tested by reliability test and validity test, then the classical assumption was tested including normality test, multicollinearity test, and heteroscedasticity test. Then hypothesis testing is done by single regression analysis and multiple regression analysisThe results show that all variables are reliable and valid and meet the classical assumption test. The results of hypothesis analysis show that obedience pressureaffects budgetary slack, there is an interaction between obedience pressureand reinforcement contingency to budgetary slack, and no interaction between obedience pressureand moral equity to budgetary slack Key Words: obedience pressure, reinforcement contingency, moral equity, budgetary slack